1988
DOI: 10.1038/clpt.1988.87
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine metabolism in human liver: Identification of a cytochrome P-450III gene family as the major cyclosporine-metabolizing enzyme explains interactions of cyclosporine with other drugs

Abstract: The rate of formation of the three initial metabolites of cyclosporine metabolism has been determined in liver microsomes of 15 kidney transplant donors. Interindividual variation in metabolite formation was considerable but all three metabolites varied in parallel. An antiserum raised against a steroid-inducible rat cytochrome P-450 (P-450 PCN) strongly inhibited the formation of these metabolites. Immunoquantitation of the protein recognized by a monoclonal antibody reacting with human cytochromes P-450 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
186
2
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(195 citation statements)
references
References 0 publications
5
186
2
1
Order By: Relevance
“…3,4 It has been identified that the metabolism of CsA is mainly mediated by cytochrome P450 3A (CYP3A). 5 Therefore, CYP3A may importantly affect CsA pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 It has been identified that the metabolism of CsA is mainly mediated by cytochrome P450 3A (CYP3A). 5 Therefore, CYP3A may importantly affect CsA pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Of them, CYP3A4 and CYP3A5 are the major enzymes accounting for metabolism of CsA. 5 CYP3A4 is abundantly and constitutively expressed in liver and intestine. 6 According to published literature, the expression of CYP3A4 is limitedly influenced by genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…leading to double-strand DNA cleavage (Tewey et al, 1984). MX2 also induces DNA double-strand breaks by the same mechanism (Horichi et al, 1990 (Kronbach et al. 1988).…”
Section: Alkaline and Neutral Elutionsmentioning
confidence: 99%
“…CYP 3A4, a P450 subfamily highly expressed in human liver, is important from a pharmacological and toxicological point of view, not only because of its relative abundance in human liver (Guengerich and Turvy, 1991) but also because it is involved in the metabolism of many widely used drugs including nifedipine (Guengerich et al, 1986a), quinidine (Guengerich et al, 1986b), erythromycin and troleandomycin (Pessayre et a]., 1982;Watkins et al, 1985;Combalbert et al, 1989;Brian et al, 1990;Renaud et al, 1990), cyclosporin A (Kronbach et al, 1988;Aoyama et al, 1989;Combalbert et al, 1989), 17 a-ethynylestradiol (Guengerich, 1988), midazolam (Kronbach et al, 1989), lidocaine (Bar- (1982,1983). getzi et al.…”
mentioning
confidence: 99%